Arylboronates as H2O2 or Photo-Inducible DNA Cross-Linking Agents: Design, Synthesis, Mechanism, and Anticancer Activity - (:unkn) unknown (My University, 2015)
Interest in the development of cancer therapies with improved selectivity and reduced host toxicity has been growing. In this thesis, we designed and synthesized a series of novel non-toxic arylboronic ester and biarylboronic ester derivatives that can be activated by hydrogen peroxide (H2O2) to induce DNA interstrand cross-link formation. The mechanism of DNA cross-linking induced by these arylboronates involves generation of phenol intermediates 1 followed by departure of leaving group (L) leading to quinone methides (QMs) 2, which directly cross-link DNA via alkylation. The QM formation is the rate-determining step for DNA cross-linking. The activity and selectivity of these compounds towards H2O2 were investigated and the activation mechanism was determined by NMR analysis and QM trapping experiments. The oxidative activation of these compounds by H2O2 produced an electron rich aromatic ring that facilitated QM formation and release of the leaving group. We also evaluated the effects of the benzylic leaving groups (L), the core structures of the arylboronates, and the aromatic substituents (R) on H2O2-induced formation of bisquinone methides (bisQMs) for DNA interstrand cross-linking. A better leaving group (Br) and stepwise bisquinone methide formation increased interstrand cross-linking efficiency. The electron-donating groups (OMe or OH) on the aromatic ring greatly favored QM formation and improved interstrand cross-link (ICL) formation. An in vitro cytotoxicity assay showed that the arylboronic esters with OMe or OH at position 4 dramatically inhibited the growth of various cancer cell lines. These findings provide essential guidelines for designing novel anticancer prodrugs. Furthermore, the photochemical reactivity of these arylboronates, including phenyl boronates and naphthalene boronates, towards DNA has been investigated. The results indicated that most arylboronates induced DNA ICL formation upon 350 nm irradiation. Two mechanisms were involved for photo-inducible DNA ICL formation: a) UV-irradiation of the arylboronates produced a methyl radical which was oxidized to a methyl cation capable of alkylating DNA; b) a methyl cation was directly generated by UV-irradiation of the arylboronates via heterolysis of CH2-L (L= Br or NMe3+Br-) bond. The activation mechanism was determined using the orthogonal traps, 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) and methoxyamine. The TEMPO reacts with free radicals while methoxyamine acts as a carbocation trap.